ANALISIS PENGARUH PENERAPAN CORPORATE GOVERNANCE, STRUKTUR KEPEMILIKAN, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERBANKAN - Andra Zeptian; Abdul Rohman (Diponegoro Journal of Accounting, 2013)
This study aimed to analyze the effect of the application of corporate governance, ownership structure, and firm size on earnings management. This study used the entire population of the banking sector companies listed on the Indonesia Stock Exchange in 2009 and 2010. Sampling was done by purposive sampling technique and obtained samples used in this study were 26 companies. The method of analysis used in this study is multiple regression. This study used the dependent variable (earnings management) and the independent variables (the proportion of independent board, audit committee, auditor quality, managerial ownership, institutional ownership, and firm size) and control variable (leverage). The results showed that the proportion of independent board and auditor quality have significantly negative effect against earnings management. Audit committee, managerial ownership, and institutional ownership are not significant against earnings management. Firm size has significantly positive effect on earnings management.